Depression and ART initiation among HIV serodiscordant couples in Kenya and Uganda - Velloza, Jennifer (AIDS Behav, 2017)
BACKGROUND: Depression is a known barrier for antiretroviral therapy (ART) adherence, but less is understood about its effects on ART initiation. METHODS: We followed 1,013 HIV-infected individuals participating in the Partners Demonstration Project, an open-label study of integrated pre-exposure prophylaxis (PrEP) and ART delivery for HIV serodiscordant couples in Kenya and Uganda. Associations between depression, measured annually with the Hopkins Symptoms Checklist-Depression (HSCL-D), and ART initiation were assessed with Cox proportional hazards regression. RESULTS: At enrollment, 162 participants (16.0%) reported symptoms consistent with probable depression, defined by a HSCL-D mean score >1.75, and this proportion decreased during study follow-up (6.7% and 3.6% at 12- and 24-months, respectively; p-value <0.001). Greater depressive symptom severity was associated with a greater likelihood of ART initiation overall (adjusted hazard ratio [aHR] 1.32, 95% CI:1.01–1.73) and among participants with CD4 count ≤350 cells/μl (aHR 1.30, 95% CI:1.01–1.67). Depression decreased six months after ART initiation (adjusted odds ratio [aOR] 0.34, 95% CI:0.23–0.51). DISCUSSION: Among East African HIV-infected persons in HIV serodiscordant couples, depression was not a barrier to ART initiation. ART initiation was associated with improved depressive symptoms in this setting.